How Do Transparency, Accountability, And Zakat Literacy Influence Muzakki Trust In Islamic Organizations? A Case Study Of Lazismu - Abid Ramadhan; Dahniyar Daud; Muh Akbar (Academic Bright Collaboration, 2026)
Purpose – This study examines the influence of financial reporting transparency, accountability in zakat fund management, and zakat literacy on muzakki trust in LAZISMu, South Sulawesi. Methods – A cross-sectional quantitative study was used. Data were collected using a structured online questionnaire, which was sent to 94 muzakki registered in the LAZISMu South Sulawesi database (N = 1,526). These muzakki were chosen through simple random sampling, with a 10% margin of error, as calculated using the Slovin formula. We used Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 to test the proposed relationships between transparency, accountability, zakat literacy, and muzakki trust. Findings – Financial reporting transparency and zakat literacy both demonstrate a statistically significant positive relationship with muzakki trust; conversely, accountability in zakat fund management does not achieve statistical significance within this particular sample. Research implications – These findings suggest that zakat organizations should prioritize accessible financial communication and invest in zakat education programs, particularly in areas with moderate literacy levels, such as South Sulawesi. However, these conclusions are limited to LAZISMu in South Sulawesi. Originality – This study offers a contextual contribution by examining LAZISMu in South Sulawesi a regionally distinct and previously under-studied institutional context characterized by comparatively lower zakat literacy scores and provides evidence-based recommendations for trust-building in regional Islamic philanthropic institutions.